A college student satisfaction: strategic analysis from factor analysis - Cadena-Badilla, Martín (2016)
This study aims to present strategies for student satisfaction based on measurement and factorial analysis of this construct ina Mexican University, using a measuring college student satisfaction (SEUing ) . This is an exploratory study based on a review of the literature. Using a non-probability sampling 100 data were collected in Industrial Engineering, from which, upon proof of sampling adequacy (determinant of correlation matrix = 8.93 x10 -6 and KMO statistic was 0.849), factor analysis was performed. Using a Varimax rotation, four dimensions were identified and were named : Teaching, Academic Organization, Campus Life, Facilities and University Services , with Internal Consistencies of α1 = 0.894; α2 = 0.869; α3 = 0.822; α4 = 0.745, respectively. Explaining 67% of the total variance, Statistical tests performed (significant at 5%) , the analysis of reliability (Cronbach’s alpha > 0.70) , demonstrate the validity and reliability of the scale used SEU.